Heterologous COVID-19 vaccinations of Covishield/Astrazenica and Pfizer/Biontech: a case report - Kolaib, Tamer M.; Sabry, Rehab M. (International Journal of Research in Medical Sciences, 2021)
The most significant scientific breakthrough in the fight against COVID-19 pandemic is the speedy creation of COVID-19 vaccinations. Despite the fact that all licensed vaccines’ efficacy and safety have been shown in large clinical trials, but the data regarding heterologous vaccination regimens’ efficiency and safety is still limited. Heterologous schedules are intriguing for a variety of reasons, including logistical and therapeutic efficacy. The approval of heterologous vaccination will give countries with limited vaccine access and countries where different vaccines may become available at different times the opportunity to make vaccination programmes more flexible in response to supply fluctuations. Heterologous regimens have the potential to elicit a greater response, resulting in increased efficacy. In this case report we presented an adult male who was inadvertently given a combination of Covishield and Pfizer COVID-19 vaccines within a 3 weeks interval period. This event happened accidentally. The patient was reassured and followed up after 8 weeks without any adverse reaction.